Disseminated herpes simplex virus infection with hepatitis in an adult renal transplant recipient. Issue 9 (September 1981) - Walker, DP; Longson, M; Lawler, W; Mallick, NP; Davies, JS; Johnson, RWG
Abstract : A rare occurrence of disseminated herpes simplex virus infection with hepatitis in an adult renal transplant recipient is described.